Selective activity of 5-fluoroorotic acid against Plasmodium falciparum in vitro. - Rathod, P K (1989)
Unlike mammalian cells, malarial parasites are completely dependent on de novo pyrimidine metabolism. Even though these parasites do not use external uracil or uridine, orotic acid, an intermediate of pyrimidine biosynthesis, is successfully transported into the parasite and incorporated into parasite nucleic acids. On this basis, it was hypothesized that 5-fluoroorotate, a cytotoxic derivative of orotic acid, may be a potent and selective antimalarial agent. In vitro, 5-fluoroorotate caused 50% inhibition of the growth of Plasmodium falciparum at a concentration of 6.0 nM. In contrast, 5-fluorouracil, 5-fluorouridine, and 5-fluoro 2'-deoxyuridine were much less effective against malarial parasites. Chloroquine-susceptible and chloroquine-resistant clones of P. falciparum were equally susceptible to 5-fluoroorotate. The toxicity of 5-fluoroorotate was evaluated on four human cell lines (HT-1080, IMR-90, HeLa S3, and HL-60) and one mouse cell line (L-1210). Compared with malarial parasites, the mammalian cells were relatively tolerant of 5-fluoroorotic acid (50% inhibitory concentration, 0.9 to 10 microM). Finally, in the presence of 1 mM uridine, all mammalian cells were partially protected from 5-fluoroorotate cytotoxicity, but uridine offered no protection to P. falciparum.